Evaluate the Load Deflection Properties of Titanium Orthodontic Archwires Coated with Zirconium: An In Vitro Study (Journal of Academic Research, 2021)
The purpose of this study was to evaluate the load deflection characteristics and analyze the compositions of two products of titanium orthodontic archwires after surface coating. Timonium titanium archwires (TIM) and beta-titanium orthodontic archwires (β-Ti III) were obtained from (3M Unitek® USA and TIM orthodontic archwires 3M and TP Orthodontics® USA). The electron beam physical vapor deposition (EB PVD) was used to coat (5, 10, 25, and 50 thick) of pouring Zr on chose archwires. The load deflection properties were assessed by the modified bending test utilizing a 3-point bend structure, the samples were held in slots with underpins 10 mm apart and displaced at the midpoint. The wires were set up as straight of lengths of 14 mm. A 3-point bending test was performed with a Hounsfield test machine. load deflection tests demonstrated significant contrasts between Zr-covered archwires coated and uncoated archwires. A high load deflection rate was shown by the coated β-Ti III archwires and a low load deflection avoidance rate was displayed by the coated TIM archwires. Load deflection test of 1 mm demonstrated comparable forces for both uncoated β-Ti III archwires and those coated with 5 nm Zr was 250g. The value for β-Ti III archwires coated with 10, 25 and 50 nm Zr, was up to 261g. In this way, the coating of 5 nm Zr on β-Ti III archwires have not shown decrease in an archwires quality while coating of 10, 25 and 50 nm Zr have displayed increments in archwires deflection force. β-Ti III archwires contain strong elements, for example, Mo and Zr and coating of 5, 10, 25, and 50 nm Zr might improve the deflection force for titanium orthodontic archwires.
Keywords: load deflection; titanium orthodontic archwires